Differential vasodilator effect of Dioclea rostrata lectin in conductance and resistance arteries: Mechanisms and glycoconjugate binding relationships. Issue 2 (30th May 2021) - Botelho, Tatiani; Osterne, Vinicius J.S.; Pinto‐Junior, Vanir R.; Oliveira, Messias V.; Cavada, Benildo S.; Nascimento, Kyria S.; dos Santos, Leonardo
Abstract: Lectins are proteins that recognize specific carbohydrates, and the vasorelaxant effect of legume lectins has been previously reported, for example the Dioclea rostrata lectin (DRL). This study evaluated major pathways of DRL‐induced relaxation in different artery segments and the possible molecular interactions involved. Rat thoracic aorta, coronary and mesenteric resistance arteries were tested "in vitro" with concentration‐response curves to DRL (0.01‐100 µg/mL). L‐NAME, indomethacin and high KCl were used to evaluate nitric oxide, cyclooxygenase and hyperpolarization‐dependent effects. DRL promoted relaxation of all vessels throughout different mechanisms. L‐NAME blunted DRL‐induced effects only in the aorta and mesenteric resistance artery. By the use of depolarizing KCl solution, vasodilation was reduced in all arteries, while incubation with indomethacin indicated a role of cyclooxygenase‐derived factors for DRL effects in mesenteric and coronary arteries, but not in the aorta. Molecular docking results suggested interactions between DRL and heparan sulphate, CD31 and other glycans present on the membrane surface. These data indicate that the mechanisms involved in DRL‐mediated vasodilation vary between conductance and resistance arteries of different origins, and these effects may be related to the capacity of DRL to bind a diversity of glycans, especially heparan sulphate, a proposed mechanoreceptor for nitric oxide synthase and cyclooxygenase activation.